Analysis of Paralogons, Origin of the Vertebrate Karyotype, and Ancient Chromosomes Retained in Extant Species. (4th March 2021) - Lamb, Trevor D
Abstract: A manually curated set of ohnolog families has been assembled, for seven species of bony vertebrates, that includes 255 four-member families and 631 three-member families, encompassing over 2, 900 ohnologs. Across species, the patterns of chromosomes upon which the ohnologs reside fall into 17 distinct categories. These 17 paralogons reflect the 17 ancestral chromosomes that existed in our chordate ancestor immediately prior to the two rounds of whole-genome duplication (2R-WGD) that occurred around 600 Ma. Within each paralogon, it has now been possible to assign those pairs of ohnologs that diverged from each other at the first round of duplication, through analysis of the molecular phylogeny of four-member families. Comparison with another recent analysis has identified four apparently incorrect assignments of pairings following 2R, along with several omissions, in that study. By comparison of the patterns between paralogons, it has also been possible to identify nine chromosomal fusions that occurred between 1R and 2R, and three chromosomal fusions that occurred after 2R, that generated an ancestral bony-vertebrate karyotype comprising 47 chromosomes. At least 27 of those ancestral bony-vertebrate chromosomes can, in some extant species, be shown not to have undergone any fusion or fission events. Such chromosomes are here termed "archeochromosomes, " and have each survived essentially unchanged in their content of genes for some 400 Myr. Their utility lies in their potential for tracking the various fusion and fission events that have occurred in different lineages throughout the expansion of bony vertebrates.